2009
DOI: 10.1111/j.1600-0609.2009.01263.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of the mTOR components Rictor and Raptor in MO7e megakaryocytic cells

Abstract: The current study shows that the mTORC1 and mTORC2 complexes have distinct, non-redundant functions in MO7e MK cell proliferation, and development. The mTOR/Rictor complex affects megakaryopoiesis by regulating nuclear division and subsequent cell cycle progression, whereas Raptor signaling protects MK cells from autophagic cell death, enabling normal megakaryopoiesis to take place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…While ribosomal S6 protein is considered a direct downstream target of PKB activity through mTOR-p70S6 signaling, we observed that although PKB phosphorylation is decreased upon inhibition of SHIP2, S6 phosphorylation is enhanced. However, mTOR signaling is complex, with positive and negative feedback loops via the mTORC1 and mTORC2 signaling complexes, and cellular levels of PKB and S6 phosphorylation are thus not always unidirectional [38]. Alternatively, SHIP2 may affect the mTOR pathway independently from PKB.…”
Section: Discussionmentioning
confidence: 99%
“…While ribosomal S6 protein is considered a direct downstream target of PKB activity through mTOR-p70S6 signaling, we observed that although PKB phosphorylation is decreased upon inhibition of SHIP2, S6 phosphorylation is enhanced. However, mTOR signaling is complex, with positive and negative feedback loops via the mTORC1 and mTORC2 signaling complexes, and cellular levels of PKB and S6 phosphorylation are thus not always unidirectional [38]. Alternatively, SHIP2 may affect the mTOR pathway independently from PKB.…”
Section: Discussionmentioning
confidence: 99%
“…43 In megakaryopoiesis, the mTOR/rictor complex affects megakaryopoiesis by regulating nuclear division and subsequent cell cycle progression, whereas raptor signaling protects cells from autophagic cell death. 44 Published work suggests that downregulation of rictor in C2C12 cells can inhibit mTORC2 signaling without inhibiting mTORC1; this prevented phosphorylation of Akt on Ser473 and stimulated protein synthesis. 12 Our data show that extensive depletion of raptor had no effect on p70S6K or rpS6 phosphorylation during myogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may have important implications for approaches aimed at selectively reducing MC burden associated with inflammation, tumorigenesis, and MC proliferative disorders. Following on the reports of the roles of mTOR in cell growth and survival in other systems, [39][40][41][42][43] rapamycin has been investigated as a potential approach to block proliferating MCs. 44 However, this may in part be because of antisurvival effects through blockade of mTORC1.…”
Section: Discussionmentioning
confidence: 99%